Dietary Calcium Requirements Do Not Differ between Mexican-American Boys and Girls. Issue 8 (28th May 2014) - Palacios, Cristina; Martin, Berdine R.; McCabe, George P.; McCabe, Linda; Peacock, Munro; Weaver, Connie M.
Abstract: Mexican Americans are an understudied ethnic group for determinants of bone health, although the risk of age-related osteoporosis is high in this rapidly growing sector of the U.S. population. Thus, the objective of the present study was to establish the dietary calcium requirements for bone health in Mexican-American adolescents by measuring calcium retention calculated from balance in response to a range of dietary calcium intakes and to determine predictors of skeletal calcium retention. Adolescents aged 12–15 y were studied twice on paired calcium intakes ranging from 600 to 2300 mg/d using randomized-order, crossover 3-wk balance studies. Skeletal calcium retention was calculated as dietary calcium intake minus calcium excreted in feces and urine over the last 2 wk of balance. A linear model was developed to explain the variation in calcium retention. Boys ( n = 20) were taller and had higher lean mass, usual dietary calcium intake, bone mineral content, and serum alkaline phosphatase compared with girls, whereas girls ( n = 20) had higher Tanner scores and greater fat mass. Calcium retention increased with calcium intake ( P < 0.0001) and did not differ by sex ( P = 0.66). In boys and girls considered together, calcium intake explained 33% of the variation in calcium retention. Serum alkaline phosphatase explained an additional 11% of the variation in calcium retention. Other variables measured, including the urine N-telopeptide of type I collagen/creatinine ratio, Tanner score, serum parathyroid hormone and 25-hydroxyvitamin D, weight, height, and body mass index, did not contribute to the variance in calcium retention. In adolescence, calcium retention in both Mexican-American boys and girls was higher than determined previously in adolescent nonHispanic white girls. This trial was registered at clinicaltrials.gov as NCT01277185.